The Influence of Career Development and Job Satisfaction on Employee Performance at the Government Office of Tukka Subdistrict, Central Tapanuli Regency - Renita Tiurmaida Panjaitan; Nelly Azwarni Sinaga; Muhammad Iqbal Batubara (Journal of Economics, Management and Accounting (JEMA), 2025)
Human resources are the most important assets of an organization, therefore their management must be carried out professionally through human resource management functions. One of the key aspects of HR management is career development and job satisfaction, which directly affect employee performance. At the Government Office of Tukka Subdistrict, Central Tapanuli Regency, there are still problems such as low motivation, suboptimal career development programs, and less than maximum job satisfaction. These conditions have an impact on employee performance, indicated by low discipline, improper division of tasks, and substandard quality of public services. This study aims to analyze the effect of career development and job satisfaction on employee performance, both partially and simultaneously. The research method used is a quantitative approach with questionnaires distributed to employees of Tukka Subdistrict. Data analysis was carried out using multiple linear regression, t-test, and F-test to determine the significance of the influence of independent variables on the dependent variable. The results show that career development and job satisfaction significantly influence employee performance, with a contribution of 65%. Partially, job satisfaction is proven to be more dominant in influencing employee performance compared to career development. Employees who feel satisfied with the work environment, reward system, and leadership support tend to have higher motivation and loyalty in their work. This finding is consistent with human resource management theory which emphasizes the importance of balancing career development and job satisfaction as efforts to improve employee performance. Thus, this research provides theoretical contributions to the development of management science as well as practical recommendations for the Tukka Subdistrict Government in improving public service effectiveness through more optimal career development and job satisfaction strategies.